Persistent room-temperature phosphorescence or high-contrast phosphorescent mechanochromism: polymorphism-dependent different emission characteristics from a single gold() complex - Wang, Xiao-Yan; Yin, Ya; Yin, Jun; Chen, Zhao; Liu, Sheng Hua (Dalton transactions : an international journal of inorganic chemistry, 2021)
Luminophores with persistent room-temperature phosphorescence (p-RTP) or effective phosphorescent mechanochromism features have significant potential applications in the field of optoelectronic materials. Until now, p-RTP and remarkable phosphorescent mechanochromism phenomena have been observed in some luminescent molecules with different molecular structures. However, separately realizing p-RTP and high-contrast phosphorescent mechanochromism in different polymorphs from a single luminophore is still a valuable and challenging topic. In this work, two polymorphs 1B and 1YG of a new gold( i ) complex with blue and yellow-green luminescence, respectively, are reported. Interestingly, 1B exhibits high-contrast phosphorescent mechanochromic behavior, while 1YG exhibits a persistent room-temperature phosphorescence effect. This is the first example of simultaneously obtaining double-purpose crystalline materials with a high-contrast phosphorescent mechanochromism or persistent room-temperature phosphorescence feature from a single luminophore. Two polymorphs 1B and 1YG of a new gold( i ) complex are reported. Interestingly, 1B exhibits high-contrast phosphorescent mechanochromic behavior, while 1YG exhibits a persistent room-temperature phosphorescence effect.